(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The concept of communicative competence The concept of "communicative competence" was first introduced by Bodalev A.A. interpreted as the ability to establish and maintain effective relationships with other people when internal resources (knowledge and skills) are available. In the sociological encyclopedia, communicative competence is defined as "... orientation to different situations of communication, based on the following. cognitive and emotional experience of a person; . ability to communicate effectively with others. constantly changing mental states, interpersonal relationships, and social environment conditions through understanding oneself and others. Kunitsina V.N. Communicative competence is simply defined as "communicative success".